A Preliminary Investigation of the Association Between Misophonia and Symptoms of Psychopathology and Personality Disorders - Cassiello-Robbins, Clair; Anand, Deepika; McMahon, Kibby; Brout, Jennifer; Kelley, Lisalynn; Rosenthal, M. Zachary (Frontiers in Psychology, 2021)
Misophonia is a condition characterized by defensive motivational system emotional responding to repetitive and personally relevant sounds (e.g., eating, sniffing, throat clearing). Preliminary research suggests that Misophonia may be associated with a range of psychiatric disorders, including personality disorders. However, very little research has used clinician-rated psychometrically validated diagnostic interviews when assessing the relationship between misophonia and psychopathology. The purpose of this study was to extend the early research in this area by examining the relationship between symptoms of misophonia and psychiatric diagnoses in a sample of community adults, using semi-structured diagnostic interviews. Results indicated higher misophonia symptoms were associated with more clinician-rated symptoms of personality disorders, but not other disorders. Anxiety partially mediated the relationship between personality disorder symptoms and misophonia. These results suggest misophonia may be associated with a range of psychiatric symptoms and highlight the role of anxiety in this poorly understood condition.